2016
DOI: 10.1097/iae.0000000000001267
|View full text |Cite
|
Sign up to set email alerts
|

Didanosine Retinal Toxicity

Abstract: Herein, we report the largest series of nine cases of peripheral chorioretinal degeneration secondary to didanosine toxicity in adults. When combined with the cases in the literature, 19 cases of didanosine toxicity, 4 of which occurred in children, were collected and analyzed. Three of the new cases presented showed clear progression of degeneration despite didanosine cessation. Newer nucleoside reverse transcriptase inhibitors may potentiate mitochondrial DNA damage and lead to continued chorioretinal degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 15 publications
5
37
0
2
Order By: Relevance
“…HAART utilises dual class, triple combinational therapy, usually 2 nucleoside/non-nucleoside reverse transcriptase inhibitors and 1 protease inhibitor (e.g. ritonavir) [7,13]. DDI-associated retinal toxicity (DART) with peripheral chorioretinal atrophy was reported as early as 1992 in a phase 2 study in 5 out of 95 children [16], and similar findings were reported amongst HIV-positive adults in 1996 [4].…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…HAART utilises dual class, triple combinational therapy, usually 2 nucleoside/non-nucleoside reverse transcriptase inhibitors and 1 protease inhibitor (e.g. ritonavir) [7,13]. DDI-associated retinal toxicity (DART) with peripheral chorioretinal atrophy was reported as early as 1992 in a phase 2 study in 5 out of 95 children [16], and similar findings were reported amongst HIV-positive adults in 1996 [4].…”
Section: Discussionmentioning
confidence: 93%
“…To date since 1992, there have been numerous reported cases of didanosine-associated retinal toxicity (DART) amongst adults [4][5][6][7][8][9][10][11]. The reported clinical findings of DART range from mild mid-peripheral pigmentary stippling to extensive patches of chorioretinal atrophy which can affect the macula in advanced cases [4][5][6][7][8][9][10][11]. Patients are initially asymptomatic, but in advanced disease, they can present with significant peripheral visual field defects and nyctalopia [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations